Center Variation and the Effect of Center and Provider Characteristics on Clinical Outcomes in Kidney Transplantation: A Systematic Review of the Evidence. Issue 1 (17th October 2017) - Tsampalieros, Anne; Knoll, Gregory A.; Fergusson, Nicholas; Bennett, Alexandria; Taljaard, Monica; Fergusson, Dean
Background: Kidney transplantation is the best treatment option for patients with end-stage renal disease. While patient-level factors affecting survival are established, the presence of variation in the management of transplant recipients remains unknown. Objective: The objective of this study was to examine center variation in kidney transplantation and identify center and provider characteristics that may be associated with clinical outcomes. Design: This is a systematic review. Data sources: Ovid Medline, Embase, and Cochrane library from inception to June 2016 were used. Study eligibility: Any study examining the association between center or provider characteristics and graft or patient survival, quality of life, or functional status were included. Results: We identified 6327 records and 24 studies met eligibility. Most studies used data registries. Characteristics evaluated include center volume (n = 17), provider volume (n = 2), provider experience (n = 1), center type (n = 2), and location of follow-up (n = 1). Outcomes assessed included graft survival (n = 24) and patient survival (n = 9). Significant center variation was described in 12 of 15 and 5 of 7 studies for graft and patient survival. There was a significant and positive association between center volume and graft and patient survival in 8 and 2 studies, respectively. Provider experience and volume were significantly associated with less allograft loss and provider volume with lower risk of death. There was no association between graft survival and location of follow-up or center type. Limitations: There was substantial heterogeneity in the variables assessed and methodology used to analyze associations. Conclusion: This systematic review found center variation in kidney transplantation. Future studies in the current era are necessary to better evaluate this important topic.